Innovation in Nutrition Promotion : Literature Analysis to Increase Community Awareness and Healthy Practices - Muhammad Amin Arigo Saci; Indah Yuliana; Fatria Harwanto (Journal of Nutrition Science, 2024)
The important role of health promotion in improving community welfare has encouraged effective innovation to increase nutritional awareness and healthy lifestyle practices. This research explores recent innovations in health promotion strategies, particularly in nutrition and health, to increase awareness and encourage positive behavioral change. Through comprehensive literature analysis, this research identifies and evaluates approaches such as technology interventions, community-based initiatives, and other new strategies. The results show that innovations such as nutrition promotion media (pop-up books, PGS cards, leaflets, nutrition puzzles, and educational videos) as well as active community participation (FGD and lunch menu practices) and empowering health workers and teachers, have succeeded in increasing knowledge. , attitudes and nutritional behavior of the community. Case studies and successful programs show real improvements in community nutrition practices. However, challenges such as limited sample size, short intervention duration, and methodological obstacles need to be overcome. Based on these findings, further research is recommended focusing on: (1) longitudinal research with larger sample sizes to understand long-term impacts; (2) exploration of contextual factors that influence program effectiveness; (3) evaluate the effectiveness of innovation for vulnerable groups such as people with disabilities or people with low education; (4) evaluation of community empowerment strategies and their impact on local health policies; and (5) exploration of cross-sectoral collaboration for holistic and sustainable nutrition promotion programs. These findings provide valuable insights for practitioners, researchers, and policymakers, and serve as a comprehensive resource for designing programs that increase nutrition awareness and encourage healthy practices in communities.